Strategy for developing human resources potential of Russian Railways - S. V. Lyukhanova; A. I. Solokhina (Вестник университета, 2024)
The article studies the human resources potential concept and its development on the example of Russian Railways, one of the largest companies in Russia. In academic and scientific literature, the human resources potential concept is often mentioned in the context of studying the enterprises competitiveness in various industries, but it remains unclear what components it consists of and what indicators can be used to assess it. The authors have conducted a terminological analysis of the concept and considered its components such as spiritual, intellectual (mental), and physical (material) resources. A system classification of indicators for assessing the human resources potential in organizations has been proposed, which constitutes the scientific novelty of the study and complements economic knowledge in this area. Russian Railways has a huge human resource, which it actively develops and analyzes (in terms of age, education, gender, and categories of employees). Nevertheless, the research has shown that in the strategic sense both development plans and reported values of human resources potential indicators reflect the whole range of identified data very narrowly, which needs to be improved, especially in the current economic situation in the country. Reporting and forecasting materials of Russian Railways available in open Internet sources were used and analyzed when doing the research.